ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN EDUGAMES IPAS MATERI DAERAHKU - Utami, Desi; Sudarmin; Ellianawati; Bambang Subali; Wahyu Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the needs of students related to learning media that accommodates the needs of edugames-based students such as quizizz in the implementation of my area material for IPAS learning subjects in grade IV Elementary School. The method used in this research is a qualitative description method with research instruments in the form of observation, interviews and questionnaires. Based on the interview, it was found that there were difficulties in conveying the material of my region in the IPAS subject. The questionnaire results strongly agreed that most students felt that interactive media increased engagement and made the learning process more enjoyable. The needs analysis obtained that the majority of fourth grade students need variations in learning methods, including the use of visual and interactive media, the needs of students can be met in edugames learning media such as quizizz material my area IPAS subjects grade IV SD. The use of edugames media such as quizizz can change the learning atmosphere to be more fun, increase the enthusiasm of students and of course attract the attention of students. .